ANALISIS EMPLOYEE ENGAGEMENT DAN JOB SATISFACTION TERHADAP TURNOVER INTENTION KARYAWAN DI SADARA RESORT: Analysis Of Employee Engagement And Job Satisfaction On Employee Turnover Intention At Sadara Resort - Artatanaya, I Gusti Lanang Suta; Dewi, Ni Wayan Manik Kristya; Waciko, Kadek Jemmy (Ganec Swara, 2025)
Human resources are a crucial asset for a company in maintaining the continuity of its business operations. Without an effective workforce, a company cannot function optimally. However, the challenge of retaining competent and qualified employees is increasing along with changing employee expectations and the dynamics of the work environment. One issue that frequently arises in an organizational context is the high rate of employee turnover, which is a major concern for management. Improving employee engagement and ensuring job satisfaction are considered effective strategies for reducing turnover intention, as both factors can strengthen employees’ psychological attachment to the organization. This study aims to examine the partial effect of employee engagement and job satisfaction on employee turnover intention at Sadara Resort, as well as to examine their simultaneous influence. The findings of this study are expected to contribute to the literature related to the relationship between employee engagement, job satisfaction, and turnover intention, particularly in the hospitality industry. The results show that employee engagement and job satisfaction have a negative and significant effect on turnover intention partially. In addition, both variables simultaneously have been shown to have a significant effect in reducing employee intention to leave the company